Features of BE-perfect grammaticalization in the person-based auxiliation system of Barese - Kapkan, Danguolė Kotryna (Kalbotyra, 2024)
This paper seeks to identify patterns of the BE auxiliary usage in the Barese perfect which features a person-based auxiliary usage pattern but does not strictly adhere to it. The analysis is based on the quantitative data from written texts in Barese. The paper presents an overview of the semantic functions of the Barese perfect along with the usage frequency of the BE auxiliary in the 3rd person, where it is not foreseen by the person-based auxiliary pattern in the perfect. The analysis shows that the 3rd person BE auxiliary in the data most frequently appears with statives and subject-oriented resultatives. These two semantic functions of the perfect coincide with the least grammaticalized values of an exclusively BE perfect in Lithuanian. This shows that the development of the BE + participle construction in Barese follows the steps that may be peculiar to the grammaticalization of BE perfects. As all uses of the Barese perfect in the data used for this study with the BE auxiliary in the 3rd person draw the system closer to the Standard Italian split-auxiliary model, these developments can be regarded not merely as the influence of Standard Italian upon the local dialect, but also as contact-induced grammaticalization.